Pengembangan SDM Berbasis Smart User dalam Memanfaatkan Media Sosial dan Penggunaan E-wallet di Era Digital - Arninda, Arninda; Budiarti, Lina; Archie, Ananda; Darusman, Darusman; Agung Madepo, Mahardika; Firmansyah, Ferdy (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This community engagement aims to develop human resources (HR) based on smart user principles in utilizing social media and E-wallets in the digital era, specifically for parent guardians in Desa Durian. The digital era demands individuals to become smarter and more adaptive in using technology, including social media and E-wallets. Social media is an effective tool for communication and information, while E-wallets facilitate financial transactions efficiently and reduce dependency on cash. Increasing digital literacy is expected to enhance the abilities and understanding of parents and guardians in leveraging technology optimally and securely. The methods of this community engagement include training sessions and direct mentoring designed to provide an in-depth knowledge of social media and E-wallet usage, covering technical, practical, ethical, and security aspects of digital technology. The outcomes of this engagement demonstrate that with appropriate training, parent guardians in Desa Durian can effectively use social media for communication and information-sharing, and utilize E-wallets for financial transactions more efficiently, thereby enhancing their daily life efficiency and effectiveness. In conclusion, developing HR based on smart user principles is crucial in facing the challenges of the digital era. Improved digital literacy enables parent guardians to better adapt to changes, harness technological opportunities, and positively impact the local community. From the evaluation results of the community engagement, it was found that 82% of participants were able to understand the training materials delivered by several speakers.